2017
DOI: 10.1155/2017/2529085
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile and Antimicrobial Susceptibility Patterns of Bacteria Isolated from Pus/Wound Swab Samples from Children Attending a Tertiary Care Hospital in Kathmandu, Nepal

Abstract: In Nepal, little is known about the microbiological profile of wound infections in children and their antimicrobial susceptibility patterns. Total of 450 pus/wound swab samples collected were cultured using standard microbiological techniques and the colonies grown were identified with the help of biochemical tests. The antimicrobial susceptibility testing was performed by Kirby-Bauer disc diffusion technique. Methicillin-resistant Staphylococcus aureus isolates were detected by using cefoxitin disc and confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
30
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 12 publications
24
30
4
Order By: Relevance
“…In this study, the pus culture positivity rate in clinically suspected cases was 59.92% which is comparable to the previous reports of Rai et al, (2017) (59%) and Trojan et al, (2016) (60.1%). The male: female distribution of pus isolates was found to be 1.30:1 while the study of Rao et al, 2014 showed 1.43:1 ratio.…”
Section: Resultssupporting
confidence: 89%
“…In this study, the pus culture positivity rate in clinically suspected cases was 59.92% which is comparable to the previous reports of Rai et al, (2017) (59%) and Trojan et al, (2016) (60.1%). The male: female distribution of pus isolates was found to be 1.30:1 while the study of Rao et al, 2014 showed 1.43:1 ratio.…”
Section: Resultssupporting
confidence: 89%
“…Endogenous infections with Staph aureus are also possible as it is present in the normal flora of the human body. Staph aureus is followed by Pseudomonas as also reported by Rai S et al 3 and Chauhan M 11 whose findings are in accordance with the present study. Mohammad A…”
Section: Discussionsupporting
confidence: 93%
“…9 The results of the present study are in accordance with other studies reported in the literature so far. The incidence of wound infection was higher in males (46%) than in females (36%) which could be explained by the fact that men in our setup are involved in professions which make them more vulnerable to trauma and injuries, also reported by Ibrar et al 5 In the present study the most common pathogen isolated from pus samples were Staph aureus also reported by Rao DR 2 , Rai S et al, 3 Tiwari P et al, 10 and Chauhan M. 11 The reason may be that the sources of Staph aureus are the health care workers, and other patients in a hospital setup. Endogenous infections with Staph aureus are also possible as it is present in the normal flora of the human body.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Children have a weak immune system, which makes them susceptible to severe infections that need appropriate treatment 12 . The chances of the indiscriminate use of antibacterials are immense if regional antibiotic sensitivity data is not available, which leads to the vicious circle of bacterial drug resistance.…”
Section: Introductionmentioning
confidence: 99%